ACTIVITIES OF NON-STATE MILITARY INSTITUTIONS: ECONOMIC ASPECT - Hryhorii Sytnyk; Larysa Komakha; Nataliia Klymenko (Baltic Journal of Economic Studies, 2024)
The subject of the study is the economic aspect of the activities of non-state military institutions (private military companies), in particular, the increased demand for the services provided by them, and the state regulation of their activities by national legislation of leading foreign countries and international acts. The methodological basis of the study is modern general scientific methods (systemic and structural, formal and logical, analysis and synthesis, induction and deduction, generalisation, comparative); special methods (historical and legal). The purpose of the study is to analyse the economic aspect of non-state military institutions, based on the analysis of scientific works, experience of leading foreign countries and international practice, as well as the analysis of domestic draft laws on legalisation of military consulting activities in Ukraine. In the course of the study, the authors analysed the works of scholars who have studied various aspects of private military campaigns (legal, economic, security) and their regulation in foreign countries, as well as international legal norms on the regulation of the activities under study. In addition, the authors critically analysed domestic draft laws on legalisation, state regulation and supervision (control) over the activities of non-state military institutions in Ukraine. As a result of the study, it was established that the emergence of draft laws on the legalisation of the activities of non-state military institutions, their state regulation and supervision in Ukraine, on the one hand, is due to the aggression of the Russian Federation against Ukraine, which began in 2014. On the other hand, the economic consequences of privatisation in many industries and the need to compare the costs of the state's functions, including security, with the benefits received. Under such conditions, the business environment has demanded the introduction of a promising business activity and business sector – military consulting. Recently, this demand has been reinforced by the availability of a significant number of highly professional military specialists with experience and willingness to participate in relevant operations, including abroad. It is also understood that the demand for the services of non-state military institutions and the possibility of starting such activities in foreign countries where they are legalised will lead to an outflow of qualified specialists for employment abroad, and a loss of human resources and state budget revenues in the form of taxes paid by military consulting entities. At the same time, the existence of such entities in the country will help to improve the level of training of military personnel in the context of Russia's large-scale armed aggression against Ukraine by attracting specialists with relevant experience and willingness to engage in this type of business activity. In the post-war period, the existence of this type of legal activity will solve the problem of employment of former military personnel who wish to continue to work officially in the military and receive decent wages, and thus reduce social tensions in the economic sector.